Development of Resistance and Enhanced Mineral Solubilization Capacity of Plant Growth Promoting Rhizobacteria (PGPRs) Native to Calcareous Soils of Lime Stone Mined Spoils - Singh, Anuj Kumar; , Jamaluddin (Indian Forester, 2011)
Two different bacterial isolates of Pseudomonas fluorescens and one isolate of Azospirillum sp. screened from calcareous soil medium exhibited greater capability for calcite rock solubilization as compared to the isolates of normal nursery soil. The well adapted native bacterial isolates solubilized the calcite rock minerals efficiently than the introduced one. The isolates when repeatedly inoculated in the calcite medium, demonstrated enhanced solubilization which indicates the development of resistance and efficient strains. Such efficient strains of plant growth promoting rhizobacteria (PGPRs) may prove effective biological tools for restoration of degraded areas and wasteland development.